2021
DOI: 10.1093/molehr/gaab017
|View full text |Cite
|
Sign up to set email alerts
|

Levels of seminal tRNA-derived fragments from normozoospermic men correlate with the success rate of ART

Abstract: Decreased fertility is becoming an important social and medical problem and the male factor is involved in at least half of infertility cases. Since conventional semen analysis provides limited prediction of male fertility, in this work we evaluated the potential use of seminal small RNAs (sRNA) as markers of semen quality in ART. Our bioinformatic analyses of available sRNA-seq databases showed that the most abundant sRNA species in seminal plasma of normozoospermic men are tRNA-derived fragments (tRFs), a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The distributional shift of small RNAs may be partially explained by the considerable in ux of tRNA fragments that reportedly occurs as maturing sperm passes through the epididymis 17 . Interestingly, a recent analysis of existing small RNA-seq databases obtained from the seminal plasma of normozoospermic males, reported that 88% of the sequences annotated as piRNAs are actually tRFs 35 .…”
Section: Sequencing Results and Gene Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributional shift of small RNAs may be partially explained by the considerable in ux of tRNA fragments that reportedly occurs as maturing sperm passes through the epididymis 17 . Interestingly, a recent analysis of existing small RNA-seq databases obtained from the seminal plasma of normozoospermic males, reported that 88% of the sequences annotated as piRNAs are actually tRFs 35 .…”
Section: Sequencing Results and Gene Mappingmentioning
confidence: 99%
“…Hua et al observed that a number of tsRNAs, rsRNAs, and miRNAs are differentially expressed in human sperm in accordance with embryo quality, despite a normal semen-parameter assessment using traditional methodology 34 . Recently, a number of tRNA fragments (5' tRF-Glu-CTC, 5' tRF-Lys-CTT, and 5'tRF-Gly-GCC) were found to be increased in the seminal plasma from male partners of couples with multiple failed ART cycles 35 . Further validation is needed to develop a clinically useful and reproducible panel of differentially expressed small RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, differences are expected to be observed between a minor subset of influential sequences. Specific seminal tRNA fragments have been linked to in vitro success ( 56 ), while piRNA processing has been associated with creation of viable sperm ( 57 ), however, functionally relevant differential expression of individual sncRNA sequences was not observed in our model of idiopathic subfertility, so we elected to focus on further interrogating the miRNA population.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al, 2011), and have been suggested as biomarkers of male infertility (Kotaja, 2014;Barbu et al, 2021;Kiani, Salehi, & Mogheiseh, 2019;Salas-Huetos et al, 2020). Additionally, sperm tsRNA, miRNA and rsRNA has recently been shown to correlate with embryo quality (Grosso et al, 2021;Hua et al, 2019;Nätt & Öst, 2020; and piRNA are involved in paternal diet induced intergenerational response (Lempradl et al, 2021). We have earlier described that a short high-sugar intervention in healthy young men synchronously increases tsRNA and rsRNA coming from the mitochondrial genome and that the increase of mt-tsRNA is positively associated with simultaneous changes in sperm motility (Nätt et al, 2019).…”
Section: Discussionmentioning
confidence: 99%